Commercialization challenges for drug eluting contact lenses. (2nd August 2020) - Lanier, Olivia L.; Christopher, Keith G.; Macoon, Russell M.; Yu, Yifan; Sekar, Poorvajan; Chauhan, Anuj
ABSTRACT: Introduction: Eye drops are commonly used for delivering ophthalmic drugs despite many deficiencies including low bioavailability and poor compliance. Contact lenses can deliver drugs with high bioavailability but commercial contacts release drug rapidly, limiting benefits and necessitating modifications to improve the drug release characteristics. Areas covered: This review covers the common approaches to prolong the release rates of drugs from contact lenses including molecular imprinting, incorporation of nano/microparticles, vitamin-E barriers, and layered/implant contact lenses. It also evaluates their suitability for commercialization and discusses challenges that need to be addressed before commercialization is possible. Expert opinion: In spite of many benefits of contact lenses compared to eye drops, a drug-eluting contact lens has not emerged in the market due to many reasons including potential safety risks, patient and practitioner acceptance, and production and storage factors. Importantly, changes in the critical lens properties must also be considered such as ion and oxygen permeability, loss in modulus, optical and swelling properties, and protein adherence upon drug loading. Many technologies have addressed scientific and commercialization challenges and are currently being tested both in animal and clinical studies. It is likely that a drug-eluting contact lens will be commercialized in the future.